Striatal Plasticity in L-DOPA- and Graft-Induced Dyskinesia; The Common Link? - Rylander Ottosson, Daniella; Lane, Emma (Frontiers in Cellular Neuroscience, 2016)
One of the major symptoms of the neurodegenerative condition Parkinson’s disease is a slowness or loss of voluntary movement, yet frustratingly therapeutic strategies designed to restore movement can result in the development of excessive abnormal movements known as dyskinesia. These dyskinesias commonly develop as a result of pharmacotherapy in the form of L-DOPA administration, but have also been identified following deep brain stimulation and intrastriatal cell transplantation. In the case of L-DOPA these movements can be treatment limiting, and whilst they are not long lasting or troubling following deep brain stimulation, recognition of their development had a near devastating effect on the field of cell transplantation for Parkinson’s disease. Understanding the relationship between these therapeutic approaches and the development of dyskinesia may improve our ability to restore function without disabling side effects. Interestingly, despite the fact that dopaminergic cell transplantation repairs many of the changes induced by the disease process and through L-DOPA treatment, there appears to be a relationship between the two. In rodent models of the disease, the severity of dyskinesia induced by L-DOPA prior to the transplantation procedure correlated with post-transplantation, graft induced dyskinesia. A review of clinical data also suggested that the worse preoperational dyskinesia causes worsened graft-induced dyskinesia. Understanding how these aberrant behaviours come about has been of keen interest to open up these therapeutic options more widely and one major underlying theory is the effects of these approaches on the plasticity of synapses within the basal ganglia. This review uniquely brings together developments in understanding the role of striatal synaptic plasticity in both L-DOPA and graft-induced dyskinesia to guide and stimulate further investigations on the important striatal plasticity.